Sterility Assurance Across-Sectors—New Paradigms and Tools - Lambert, Byron J.; Hansen, Joyce M.; Bryans, Trabue D.; Lam, Stan (Frontiers in Medical Technology, 2021)
The sterility assurance community is facing significant challenges. A relatively recent challenge is the pressure on manufacturing supply chains resulting from the limited availability of capacity for terminal sterilization of healthcare products. The current challenge is finding solutions for innovative new products, especially biologics and combination products, that offer great promise for patients around the world. This challenge will become more prevalent in the future as products advance. This article frames new paradigms and tools being developed to address these challenges. Foundational principles and current realities from each sector are reviewed so that sterility assurance professionals have a solid base from which to build strategies.